The Weight of Love: Affect, Ecstasy, and Union in the Theology of Bonaventure - Davis, Robert (Fordham University Press, 2016)
Supplementing theological interpretation with historical, literary, and philosophical perspectives, 'The Weight of Love' analyzes the nature and role of affectivity in medieval Christian devotion through an original interpretation of the writings of the Franciscan theologian Bonaventure. It intervenes in two crucial developments in medieval Christian thought and practice: the renewal of interest in the corpus of Dionysius the Areopagite in thirteenth-century Paris and the proliferation of new forms of affective meditation focused on the passion of Christ in the later Middle Ages. Through the exemplary life and death of Francis of Assisi, Robert Glenn Davis examines how Bonaventure traces a mystical itinerary culminating in the meditant’s full participation in Christ’s crucifixion. For Bonaventure, Davis asserts, this death represents the becoming-body of the soul, the consummation and transformation of desire into the crucified body of Christ